Invarianza factorial y temporal del Cuestionario de Regulación Emocional (ERQ) - Pineda, David; Valiente, Rosa M.; Chorot, Paloma; Piqueras, José A.; Sandín, Bonifacio (Revista de Psicopatología y Psicología Clínica, 2018)
Abstract: Factorial and temporal invariance of a Spanish version of the Emotional Regulation Questionnaire (ERQ). The Emotional Regulation Questionnaire (ERQ; Gross y John, 2003) is widely used to assess individual differences in reappraisal and suppression strategies of emotion regulation. The present study tests the factorial and temporal invariance of a Spanish adaptation of the ERQ on two samples of 1.980 participants aged 18–67 years. Psychometric properties, reliability, and factorial and temporal validity of the ERQ were calculated. Results of the confirmatory factor analysis showed the expected two-factor structure. Results also indicated adequate internal consistency, test-retest reliability, and convergent and discriminant validity. As expected, reappraisal use was positively associated with positive emotion and negatively with negative emotion, whereas suppression use was negatively associated with positive emotion and positively with negative emotion. These findings suggest that the Spanish version of the ERQ is a valid and reliable instrument for evaluating strategies of emotion regulation in the Spanish-speaking population. Resumen: El Cuestionario de Regulación Emocional (ERQ; Gross y John, 2003) es ampliamente utilizado para evaluar las diferencias individuales en las estrategias de regulación emocional reevaluación y supresión. El presente estudio examina la invarianza factorial y temporal de una adaptación española del ERQ en dos muestras de 1.980 participantes de 18-67 años de edad. Examinamos su fiabilidad, y validez factorial y temporal. El análisis factorial confirmatorio reflejó una estructura de dos factores. También encontramos niveles adecuados de consistencia interna, fiabilidad test-retest, y validez convergente y discriminante. Como se esperaba, el uso de la reevaluación se asoció positivamente con las emociones positivas y negativamente con las emociones negativas, mientras que la supresión se asoció a un patrón opuesto. Estos datos sugieren que la versión española del ERQ es un instrumento válido y fiable para evaluar las estrategias de regulación emocional en población de habla española.